Cidades dispersas e aldeias virtuais no pós-pandemia da Covid-19 - Ferrás Sexto, Carlos (Finisterra, 2021)
We reflect on the concepts of the dispersed city, the virtual village, and the revolution in information and marketing in the new scenario that Covid-19 and the Post-Pandemic has begun to draw. We ask ourselves about the effects that these phenomena have on the relations between the urban and rural world, and we present a debate on the problems and the opportunities that this entails for territorial planning and public health.